PEP and TasP Awareness among Italian MSM, PLWHA, and High-Risk Heterosexuals and Demographic, Behavioral, and Social Correlates. - Gabriele Prati; Bruna Zani; Luca Pietrantoni; Diego Scudiero; Patrizia Perone; Lella Cosmaro; Alessandra Cerioli; Massimo Oldrini (PLoS ONE, 2016)
Post-exposure prophylaxis (PEP) has been proposed as a strategy to prevent the acquisition of HIV infection after certain high-risk exposures, and treatment as prevention (TasP) is also being advocated as a means to reduce sexual transmission of HIV. The aim of this study was to investigate the prevalence of PEP and TasP awareness and their demographic, behavioral, and social correlates in Italy. We conducted a cross-sectional survey of 1,028 high-risk heterosexual men and women, 1,874 non-HIV positive MSM (men who have sex with men), and 694 people living with HIV/AIDS (PLWHA). The majority of the participants was aware of PEP and unaware of TasP. MSM were less knowledgeable about PEP and TasP than were PLWHA and more knowledgeable about PEP and TasP than were high-risk heterosexual participants. The variables most consistently associated with PEP and TasP awareness were contact with HIV/AIDS organizations, HIV testing, and HIV stigma. A positive relationship between unprotected sexual intercourse and PEP and TasP awareness was found among high risk heterosexual participants, while this association was not significant among MSM and PLWHA. Because PEP and TasP are currently recommended, effective educational and dissemination strategies are needed to increase the level of knowledge about PEP and TasP.